2022
DOI: 10.3389/fpls.2022.787265
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Triacylglycerol Overproduction in the C4 Bioenergy Crop Sorghum bicolor by Constraint-Based Analysis

Abstract: Upregulation of triacylglycerols (TAGs) in vegetative plant tissues such as leaves has the potential to drastically increase the energy density and biomass yield of bioenergy crops. In this context, constraint-based analysis has the promise to improve metabolic engineering strategies. Here we present a core metabolism model for the C4 biomass crop Sorghum bicolor (iTJC1414) along with a minimal model for photosynthetic CO2 assimilation, sucrose and TAG biosynthesis in C3 plants. Extending iTJC1414 to a four-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…9% (DW) was achieved 4 d after induction provides support for rapid TAG accumulation at or close to the end of vegetative growth (Liang et al ., 2023). Further support for the idea of inducing TAG accumulation late in development comes from metabolic modeling in which it is estimated that Sorghum could accumulate 20% TAG DW in its vegetative tissues in 28 d at the end of the growing season if only 5% of net carbon assimilation was consumed for oil synthesis (Clark & Schwender, 2022). In addition to achieving the optimal balance of expression of lipogenic factors, other approaches may help reduce yield drag, such as the expression of purple acid phosphatase2 (Cai et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…9% (DW) was achieved 4 d after induction provides support for rapid TAG accumulation at or close to the end of vegetative growth (Liang et al ., 2023). Further support for the idea of inducing TAG accumulation late in development comes from metabolic modeling in which it is estimated that Sorghum could accumulate 20% TAG DW in its vegetative tissues in 28 d at the end of the growing season if only 5% of net carbon assimilation was consumed for oil synthesis (Clark & Schwender, 2022). In addition to achieving the optimal balance of expression of lipogenic factors, other approaches may help reduce yield drag, such as the expression of purple acid phosphatase2 (Cai et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the engineering strategy could be to divert the C flow away from sucrose export towards oil synthesis (Figure 3). A recent theoretical modeling study on Sorghum bicolor found that, based on daily rates of net CO 2 photo-assimilation observed for mature leaves under field conditions, TAG could accumulate to a 20% (w/dw) level in less than a month (Clark & Schwender, 2022). However, this goal could only be accomplished if 5% of the photo-assimilated C was diverted towards oil accumulation, and futile cycles of lipid biosynthesis and degradation operated on a massive scale, which would significantly impede the overall photo-assimilation (Clark & Schwender, 2022).…”
Section: Use Of Stable Isotopes To Assess the Production Of High-valu...mentioning
confidence: 99%
“…A recent theoretical modeling study on Sorghum bicolor found that, based on daily rates of net CO 2 photo‐assimilation observed for mature leaves under field conditions, TAG could accumulate to a 20% (w/dw) level in less than a month (Clark & Schwender, 2022). However, this goal could only be accomplished if 5% of the photo‐assimilated C was diverted towards oil accumulation, and futile cycles of lipid biosynthesis and degradation operated on a massive scale, which would significantly impede the overall photo‐assimilation (Clark & Schwender, 2022). In many cases, reported TAG levels are substantially below a 20% w/dw level, although some plants such as Nicotiana tabacum have been engineered to produce TAG levels above 30% w/dw level (Box S4).…”
Section: Feedstock Developmentmentioning
confidence: 99%